Development of TPACK Integrated Learning Tools on Aqidah Akhlak Learning Materials for Class XII Madrasah Aliyah Students - Rohman, Dalia Farahillah; Roziqin, Muhamad Khoirur; Putra, Ino Angga; Hidayatulloh, Dimas; Abdillah, Afif (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
One of them is learning that must be integrated with existing science and technology so that it becomes a demand for teachers to improve their competence, especially using technology in learning. One type of learning that includes the interaction of teachers, students, and technology is the TPACK (Technology, Pedagogical, Content, Knowledge) learning model. The research aims to determine the design and feasibility of the TPACK integrated learning tool in the Aqidah Akhlak lesson material for Class XII MAN 3 and MA Al-Bairuny students. This research uses a development research method according to the 10 stages of Brog and Gall. This research is limited to 5 stages and does not reach the implementation stage. Data was collected using a validation sheet which was assessed by 5 validators and data analysis was carried out through product feasibility testing. The research results showed that the TPACK integrated learning tools in the form of RPP and LKPD were very suitable for use according to the product validation results of 87%. There needs to be improvements related to adjusting time allocation in learning. Researchers hope that in the future further research can be carried out to see the effectiveness of this learning tool in the classroom.